International case studies of terrorist rehabilitation - Gunaratna, Rohan; Hussin, Sabariah (Routledge studies in the politics of disorder and instability, 2018)
"The post 9/11 era has produced structured rehabilitation programs in a wide range of countries including Saudi Arabia, Singapore, Pakistan, Malaysia, Egypt, Iraq, and Uzbekistan. There are also ad hoc and emerging programs in Nigeria, China, Indonesia, Bangladesh, Denmark, Germany, United Kingdom and Nepal. Due to the threat from global Islamist terrorist groups, including Al-Qaeda and the Islamic State (IS), the focus has tended to be on Islamist groups. However, Sri Lanka also has a multi-faceted rehabilitation program that was created after the ethno-nationalist Liberation Tigers of Tamil Eelam (LTTE) group was defeated in 2009, which can teach us some valuable lessons. This book consists of a series of case studies of different terrorist rehabilitation initiatives that have been attempted around the world. Each initiative is critically analysed to develop a sound understanding of the significance of different approaches and strategies of terrorist rehabilitation in helping potential terrorists integrate back into society. Sharing and examining case studies, both by practitioners and scholars, this book provides vital tools to address the challenges faced by practitioners of terrorist rehabilitation programs"--